155. Evaluation and comparison of geometrical set-up uncertainties in hypofractionated prostate cancer radiotherapy using two different immobilization systems. (December 2018) - Rambaldi Guidasci, G.; Piergentili, M.; Zefiro, D.; Ferrando, O.; Verzanini, E.; Foppiano, F.
Abstract : Purpose: In 2015 a robotic table with six degrees of freedom (Hexapod, Elekta) was installed at our institution and has been introduced in our clinical practice. The aim of this work is to determine and compare the patient inter-fraction set-up error in prostate cancer radiotherapy using two different immobilization systems: ConFeet which is not compatible with Hexapod and Combifix, which instead, using only the cushions without the baseplate, is compatible with Hexapod. Methods: Twenty-six prostate cancer patients have been treated at our institution between July and November 2017 either with IMRT or VMAT. The patients were divided into two groups based on the type of immobilization used for their treatment. Thirteen patients were immobilized with ConFeet and thirteen with Combifix. The prostate position was assessed before each fraction, through grey scale matching between the reference CT and the online acquired CBCT image. A total of 675 CBCT has been used for this analysis. The corrections were registered for the three principal axes, left-right(X), supero-inferior(Y), antero-posterior(Z), and for the three rotational angles pitch, roll and yaw. Results: The values obtained for the two groups are shown in the Table and Figure. The prostate translation in the vertical axis(z) and the pitch have a greater systematic and random error, for both groups. Statistically significant difference between the two immobilization systems is observed for the roll, the yaw and the translations in the y and z axis. Differences were verified using t-test and Mann–Whitney's test and considered significant if the p-value was under 0.05. Conclusions: ConFeet appears to be more precise, but the combination Combifix with Hexapod still remains the favorited immobilization method, since it allows submillimetre and rotation correction. A study evaluating the set-up residual error and the impact of the translation and rotation errors on the dosimetric distribution is ongoing.